Reduced growth in Baltic Sea cod may be due to mild hypoxia. (10th April 2020) - Brander, Keith
Abstract: Daily food consumption by small Baltic Sea cod has declined in recent decades, resulting in reduced growth and biomass. Declining oxygen may cause lower production of benthic prey for small cod, but an alternative explanation presented here is that the mildly hypoxic conditions that small cod experience reduces their rate of digestion and hence food consumption. Better information about the distribution and behaviour of small cod and their metabolic response to low oxygen levels is required.